Effects Of Feminine Values And Communication Competence Of The Women Pr Role In Company - Zubair, Agustina (2015)
The difference between men and women in the workplace appears on the role, function and treatment. The woman, condition and their job in Indonesia is as follows. This research was conducted in Jakarta because Jakarta as a city with varies of problems in economic, social, cultural, security, and demographic conditions, demanding the metropolitan women in more competence to be competitive and still exist.